Databases for the study of entrepreneurship (Advances in entrepreneurship, firm emergence and growth, 2001)
Introduction / Jerome A. Katz -- Using census bureau data by firm size, 1988-1996 / Bruce D. Phillips -- National panel study of U.S. business startups : background and methodology / Paul D. Reynolds -- Using a household sampling frame to study family businesses : the 1997 national family business survey / Ramona K.Z. Heck, Cynthia R. Jasper, Kathryn Stafford, Mary Winter, Alma J. Owen -- Arthur mass mutual American family business survey 1995 and 1997 / Joseph H. Astrachan, Kathy Lund Dean -- The Kauffman financial statements database / Larry W. Cox, S. Michael Camp, Donald L. Sexton -- Small business economic trends : a quarter century longitudinal data base of small business economic activity / William J. Dennis, William C. Dunkelberg -- Mow research programs / S.Antonio Ruiz-Quintanilla, Rie Claes -- The usefulness of the general social surveys database in entrepreneurship and small business research / Janice J. Jackson -- Panel study of income dynamics : uses for the small business researcher / Pamela M. Williams, Jerome A. Katz -- Women entrepreneurs opportunities for database research / Candida G. Brush, Linda F. Edelman -- The logic and opportunities of secondary analysis in entrepreneurship research / Jerome A. Katz -- New data for dynamic analysis : the longitudinal establishment and enterprise microdata / Alicia Robb